Position Uncertainty in a Prisoner's Dilemma Game: An Experiment - Chowdhury Mohammad Sakib Anwar; Konstantinos Georgalos; Sonali SenGupta (Queen's University Belfast, Queen's Business School, 2025)
Gallice and Monzón (2019) present a natural environment that sustains full cooperation in one-shot social dilemmas among a finite number of self-interested agents. They demonstrate that in a sequential public goods game, where agents lack knowledge of their position in the sequence but can observe some predecessors' actions, full contribution emerges in equilibrium due to agents' incentive to induce potential successors to follow suit. Furthermore, they show that this principle extends to a number of social dilemmas, with the prominent example that of the prisoner's dilemma. In this study, we experimentally test the theoretical predictions of this model in a multi-player prisoner's dilemma environment, where subjects are not aware of their position in the sequence and receive only partial information on past cooperating actions. We test the predictions of the model, and through rigorous structural econometric analysis, we test the descriptive capacity of the model against alternative behavioural strategies, such as conditional cooperation, altruistic play and free-riding behaviour. We find that the majority resorts to free-riding behaviour, around 30% is classified as Gallice and Monzón (2019) types, followed by those with social preference considerations and the unconditional altruists.
Keywords: C91; D64; H41; 330; Position uncertainty; Conditional cooperation; Social dilemma; Social preferences; Experiment; Finite mixture models